AIE conjugated polyelectrolytes based on tetraphenylethene for efficient fluorescence imaging and lifetime imaging of living cells. Issue 26 (14th June 2017) - Gao, Mengxia; Hong, Yuning; Chen, Bin; Wang, Yinan; Zhou, Wenjun; Wong, Wallace W. H.; Zhou, Jian; Smith, Trevor A.; Zhao, Zujin
Abstract : New conjugated polyelectrolytes based on tetraphenylethene are prepared, which show good performance in fluorescence imaging and fluorescence lifetime imaging of living cells. Abstract : A series of new conjugated polyelectrolytes (CPEs) containing tetraphenylethene units are synthesized and characterized. They show apparent aggregation-induced emission (AIE) characteristics and give fluorescence covering from cyan to red with high emission efficiencies in aggregates. These AIE CPEs can directly enter and stain living cells for fluorescence imaging with low cytotoxicity, and can provide information on cellular viscosity at different locations based on fluorescence lifetime imaging.